Sejarah sebagai Sekolah Moral Versus Supermarket Sekolah Abad XXI dan Memudarnya Kesejatian Hidup - Nengah Bawa Atmadja, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This article reviews the phenomenon of moderneducation, particularly highlighting the behavior ororientation of society that ignores history as a school ofmoral or political virtue in society and state. Withoutthe presence of the government so that the symptomslooping symbolic violence. Second, look for strategicsteps that can be done so that the function of history as amoral school optimal.Kajian can run against both of theseissues are very fundamental and must be understood asthe historical background of the dysfunctional moralschool. School morale is an important part of findinga solution. By using the approach of cultural studies,the teaching of history can be directed and contributedideal text and social text in order to overcome variousproblems.
Keywords: history; moral schools; supermarkets schools; the teaching of history